Case studies of gender equality and social inclusion success stories in Zambia's agribusiness sector - Akamandisa, Vincent M.; Alamu, Emmanuel Oladeji; Cole, Steven M.; Chikoye, David (2023)
This report presents case studies of success stories of value chain actors who operate in Zambia’s agribusiness sector to promote gender equality and social inclusion. Potential success stories were identified during a stakeholder workshop on gender equality and social inclusion in the agribusiness ecosystem for multidimensional mapping of opportunities and challenges held in September 2022 in Lusaka. Some of these stories were then selected from different value chains for follow-up by the research team. Interviews with the value chain actors in these stories were arranged and conducted in early 2023.